2019
DOI: 10.1111/andr.12656
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms and possible immune therapy in testicular germ cell tumours

Abstract: Background: Testicular germ cell tumours (GCTs) are the only universally curable solid malignancy. The long-term cure rate of >95% is attributed to the extraordinary sensitivity to cisplatin-based treatment but a proportion of patients die due to a progression of the chemotherapy-refractory disease. While treatment of a variety of solid cancers was significantly improved with recent immune therapies, the immunology and immunotherapy remained underinvestigated in GCTs. Objectives: In this narrative review, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…The efficacy of immune checkpoint inhibitors as reported in available case reports and clinical trials is summarized in Table 2. These data are reviewed in the work of Semaan et al (7,44). Briefly, Shah et al reported the clinical response of patients with embryonal cell carcinoma following a single dose of anti-PD-1 immunotherapy.…”
Section: Anti-pd-1/pd-l1 Inhibitors In Tgctsmentioning
confidence: 99%
“…The efficacy of immune checkpoint inhibitors as reported in available case reports and clinical trials is summarized in Table 2. These data are reviewed in the work of Semaan et al (7,44). Briefly, Shah et al reported the clinical response of patients with embryonal cell carcinoma following a single dose of anti-PD-1 immunotherapy.…”
Section: Anti-pd-1/pd-l1 Inhibitors In Tgctsmentioning
confidence: 99%
“…While in the past GCT have long been considered to mimic testicular immune privilege, consolidating evidence has revealed infiltration of activated cytotoxic and memory T cells as well as macrophages predominately in seminoma with helper T cells and natural killer (NK) cells being rarely present [10][11][12][13]. Although preliminary immunotherapy trials with immune checkpoint inhibitors have been initiated with the aim to overcome immune escape, efficacy has been limited as yet [14,15]. Of note, beyond these efforts, data from either in vitro or in vivo studies exploring the susceptibility of GCT to immune cell-mediated cytotoxicity are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent advances in immunotherapies for cancer treatments, attention has been directed towards these anti-PD-1/anti-PD-L1 agents [ 173 , 174 ]. The immune microenvironment of TGCTs is particularly rich and distinct among subtypes [ 35 , 175 ], and the immunoexpression of immune checkpoints was demonstrated to have prognostic significance [ 176 , 177 ].…”
Section: Seeking For Novel Treatments Options For Cisplatin-resistmentioning
confidence: 99%